(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Artificial Intelligence is one of the most important innovations of the present age. By developing deep learning and machine learning techniques, nowadays it’s possible to create intelligent systems, which are able to learn new data from their own experience and to take more autonomous decisions. These intelligent technologies can be effectively used to profile people who interact with AI systems, in order to understand users’ interests and preferences and offer them more personalized products and information. This paper aims at analysing AI use in the public and political context. The application of intelligent tools, which can filter and personalize news and information, could seriously affect the pluralistic dimension which characterize modern constitutional democracies.